2019
DOI: 10.1097/md.0000000000014504
|View full text |Cite
|
Sign up to set email alerts
|

Impact of inflammation-mediated myocardial fibrosis on the risk of recurrence after successful ablation of atrial fibrillation – the FIBRO-RISK study

Abstract: Introduction:Interventional ablation has been demonstrated to represent an effective therapy in patients with atrial fibrillation (AF), leading to restoration and maintenance of sinus rhythm in the majority of cases. However, recurrence of AF is encountered in 35% to 40% of cases, and the causes for this frequent complication have not been elucidated so far.Material and methods:Here we present the study protocol of the FIBRO-RISK trial, a prospective, single-center, cohort study which aims to investigate the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 30 publications
(31 reference statements)
0
13
0
Order By: Relevance
“…The systemic inflammatory response after coronary artery bypass grafting is correlated with AF occurrence (35). In the FIBRO-RISK study, biomarkers of inflammation and myocardial fibrosis were validated as predictors for AF recurrence (36). Elevated inflammatory biomarkers levels in serum are correlated with prevalence and prognosis of AF (37,38).…”
Section: Evidence Of a Relationship Between Systemic Inflammation And Afmentioning
confidence: 99%
“…The systemic inflammatory response after coronary artery bypass grafting is correlated with AF occurrence (35). In the FIBRO-RISK study, biomarkers of inflammation and myocardial fibrosis were validated as predictors for AF recurrence (36). Elevated inflammatory biomarkers levels in serum are correlated with prevalence and prognosis of AF (37,38).…”
Section: Evidence Of a Relationship Between Systemic Inflammation And Afmentioning
confidence: 99%
“…High-sensitivity C-reactive protein levels were also lower among patients undergoing AFCA in the COVID-19 era than those in the pre-COVID-19 era. Importantly, up-regulation of inflammatory biomarkers has been shown to be a valid predictor for AF recurrence ( 13 , 14 ), and inflammation is known to alter atrial electrophysiology and structure to increase vulnerability to AF ( 15 ). Thus, changes in alcohol habits and systemic inflammation during the period of COVID-19 pandemic and associated social distancing might partly explain the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Other biophysical strategies should also be considered during ablation because epicardial fat can interfere with radiofrequency delivery to the underlying myocardial tissue 121 . The Fibro‐Risk study revealed the inflammatory role of epicardial fat in myocardial fibrosis and AF recurrence after ablation 122 . Future modulation of epicardial fat quality might improve the non‐pharmacological therapeutic strategic outcomes; this is because structural and electrical reverse remodeling of the LA was observed 2 months after PV isolation in patients with permanent AF 123 …”
Section: Af Treatmentmentioning
confidence: 99%